Comparison between Pollution Index and STORET Methods in Determining Post-Mining Lake Water Quality in Lati Petangis Forest Park, Paser, East Kalimantan after Reclamation: Methods in determining post-mining kake water quality - PUTRA, NAUFAL HAFIDH MAHDI SUJARWO; SOEPROBOWATI, TRI RETNANINGSIH; JUMARI, JUMARI (Borneo Journal of Resource Science and Technology, 2024)
Tahura Lati Petangis is post-mining forest park area. Tahura Lati Petangis has been through the stages of reclamation and post-mining lake has been formed. Monitoring activities are needed to determine the success of post-mining management. This research aims to evaluate the post-mining lake of water quality in Tahura Lati Petangis based on the Pollution Index and STORET methods. The research was located at 3 observation stations, which were station 1 (Pit Lake I Saingprupuk Erai), station 2 (Natural Lake Gentung Dayo), and station 3 (Pit Lake II Saingprupuk Duo). At all research stations, in-situ water quality observations were made in the form of dissolved oxygen, pH, and water temperature at 4 points sites. Water sampling was also carried out at 4 sites in each station for ex-situ quality testing. Water quality analysis based on pollution index and STORET method. The determination of water quality status based on Government Regulation No. 22/2021. The results showed that the water quality status between Pollution Index and STORET had differences. The STORET method shows more polluted results. The source of pollution at the three observation stations is generally related to organic compounds through high measurement of chemical oxygen demand, biological oxygen demand, phosphate, and phenol, so the value of dissolved oxygen is also affected. Especially for zinc and iron dissolved in Station 3 which are heavy metals included in the accumulation of STORET scoring. Station 1 and Station 2 are only suitable for agricultural or irrigation activities (class IV), while Station 3 is not suitable for all four use classes. Therefore, Station 3 is more polluted than the other two lakes. Monitoring the water quality of post-mining lakes after reclamation showed decrease in heavy metal concentrations, and on the other side there was increase in the concentration of aquatic organic compounds.